REVIEW OF THE BOOK “ESSENTIALS OF TIBETAN TRADITIONAL MEDICINE” BY THINLEY GYATSO & CHRIS HAKIM - Singh, Narendra (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The book describes treatments conforming to the needs of people of Tibet.